hw6q8 - = ¬(¬(¬A • B • ¬(¬(¬B • C • ¬(¬B...

Info iconThis preview shows page 1. Sign up to view the full content.

View Full Document Right Arrow Icon
NAND Gate Reduction = (¬A • B) + (B + ¬C) = ¬(¬(¬A • B) • ¬(B + ¬C)) = ¬(¬(¬A • B) • ¬(¬(¬B • C))
Background image of page 1
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: = ¬(¬(¬A • B) • ¬(¬(¬B • C) • ¬(¬B • C))...
View Full Document

{[ snackBarMessage ]}

Ask a homework question - tutors are online